2022
DOI: 10.1155/2022/2462077
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Information Flows among Developed and Emerging Equity Markets

Abstract: We rely on daily changes in implied volatility indices for the US stock market (VIX), developed markets excluding the US (VXEFA), stock markets in Brazil (VXEWZ), Russia (RVI), India (NIFVIX), China (VXFXI), and the overall emerging market volatility index (VXEEM) to examine the degree of information flows among the markets in the coronavirus pandemic. The study also employs the complete ensemble empirical mode decomposition with adaptive noise (CEEMDAN) to decompose the data into intrinsic mode functions (IMF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 78 publications
(109 reference statements)
1
4
0
Order By: Relevance
“…Finally, low frequencies are defined as mean periods longer than 50 days. This is consistent with the empirical approach by Adam et al (2022, Owusu Junior et al (2021b, Asafo-Adjei et al (2022c), Asafo-Adjei et al (2022b) and Bossman et al (2022a).…”
Section: Preliminary Statisticssupporting
confidence: 91%
See 1 more Smart Citation
“…Finally, low frequencies are defined as mean periods longer than 50 days. This is consistent with the empirical approach by Adam et al (2022, Owusu Junior et al (2021b, Asafo-Adjei et al (2022c), Asafo-Adjei et al (2022b) and Bossman et al (2022a).…”
Section: Preliminary Statisticssupporting
confidence: 91%
“…Further, the time-varying dynamics of the financial markets were amplified as they reported that investors who delayed investment in these markets during the pandemic were likely to minimize risks. Boateng et al (2022b) also employed the CEEMDAN-based RTE framework to quantiify information flows among developed and emerging equity markets. In their findings, they found a mixture of bi-directional and uni-directional flow of both high-and low-risk information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, the existence of crises or economic events has given rise to addressing the important role a market-based system plays in responding to or influencing other macroeconomic fundamentals, leading to their interdependent structures. The rise in correlations between the market-based system and other macroeconomic variables during turbulent periods contributes to the contagion literature (Baur 2012;Shahbaz et al 2019;Boateng et al 2022b;Agyei et al 2022b;Bossman et al 2022aBossman et al , 2022bYarovaya et al 2022;Gunay and Can 2022, etc. ).…”
Section: Comovements Between Market-based System and Macroeconomic Va...mentioning
confidence: 99%
“…Accordingly, the roles of exchange rate and interest rate can be factored to contribute to the understanding of the macroeconomic modelling. Considering the rapid fluctuations in financial time series leading to their nonlinearities, analyses can also be performed using robust decomposition techniques coupled with the quantification of the amount of information that flows through the macroeconomic variables [ [76] , [77] , [78] , [79] , [80] , [81] , [82] ]. The sample period is limited to August 2021 due to limited data availability for some variables for the G8 nations but enough for the subject matter to be investigated.…”
Section: Conclusion and Policy Recommendationmentioning
confidence: 99%